2016
DOI: 10.1002/per.2051
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Personality, Betrayal Trauma, and Leukocyte Telomere Length in Adulthood: A Lifespan Perspective on Conscientiousness and Betrayal Traumas as Predictors of a Biomarker of Cellular Ageing

Abstract: Conscientiousness is associated with longevity. As such, identifying the biological pathways linking personality to mortality is important. This study employs longitudinal data spanning >40 years to test prospective associations with Leukocyte Telomere Length (LTL), a potential marker of cellular aging. Because telomeres shorten over time, and are sensitive to oxidative stress, shorter LTL may reflect cumulative damage associated with negative health behaviors and past stressful events. We investigated childho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 77 publications
(96 reference statements)
0
12
0
Order By: Relevance
“…Many psychiatric disorders, such as major depressive disorder (MDD), bipolar disorder (BD), post-traumatic stress disorder and schizophrenia have shown correlation to shorter leukocyte TL (40,(55)(56)(57)(58)(166)(167)(168). A recent meta-analysis confirmed these findings in patients with MDD (169), a syndrome of "premature aging".…”
Section: Telomeres As a Biomarker In Psychiatric Disordersmentioning
confidence: 98%
See 1 more Smart Citation
“…Many psychiatric disorders, such as major depressive disorder (MDD), bipolar disorder (BD), post-traumatic stress disorder and schizophrenia have shown correlation to shorter leukocyte TL (40,(55)(56)(57)(58)(166)(167)(168). A recent meta-analysis confirmed these findings in patients with MDD (169), a syndrome of "premature aging".…”
Section: Telomeres As a Biomarker In Psychiatric Disordersmentioning
confidence: 98%
“…Environmental factors, such as smoking and physical activity, have been shown to be significantly correlated to shortening of TL (52)(53)(54), as well as traumatic events or certain psychiatric illnesses (55)(56)(57)(58). In addition, studies on diseases' risk factors, such as obesity, lipid profiles and hypertension have shown some inconsistent results.…”
Section: Determinants Of Tlmentioning
confidence: 99%
“…Previously, Klest, Freyd, Hampson, and Dubanoski, (2013) demonstrated an association between trauma and self-rated physical health for participants in the Hawaii cohort. Edmonds, Hampson, Côté, Hill, and Klest (2015) reported on the relations among childhood trauma, childhood conscientiousness, and leukocyte telomere length (a potential marker of cellular aging), in the Hawaii cohort. The current study differs from these previous investigations by examining hypotheses concerning associations between child and adult personality and trauma experience, and between trauma and objective physical-health outcomes.…”
Section: The Present Studymentioning
confidence: 99%
“…Betrayal trauma theory suggests that negative experiences that impact trust in relationships, such as abusive behavior from parents, should be more problematic than adverse experiences that do not involve betrayal (Freyd, 1996). Research has shown that these events, referred to as high betrayal traumas (HBTs; Goldberg & Freyd, 2006), can hold negative impacts on health and well-being decades later (Edmonds et al, 2016; Klest et al, 2013). These studies follow a broad literature establishing that adverse childhood events typically hold negative consequences for later well-being (e.g., Chapman et al, 2004; Felitti et al, 1998).…”
Section: Adolescent Trauma Predicting Sense Of Purpose In Middle-to-lmentioning
confidence: 99%